Model evidence for distinct origins of glacial–interglacial and millennial signals in Greenland dust - Peter O. Hopcroft; Denis-Didier Rousseau (Proceedings of the National Academy of Sciences, 2026)
Greenland ice-core records show that the mineral dust flux during the last glacial maximum was twenty times greater than present and it responded rapidly during North Atlantic abrupt climate events. Both glacial–interglacial and rapid modes of dust variability have been suggested to originate from changes in storminess over Asian deserts. However, geochemical measurements do not rule out sources in Africa and Europe, and rapid changes in the source strength over Asia are yet to be unambiguously identified in North Pacific dust flux records. With a suite of Earth System model simulations of the last glacial period we show that latitudinal rainbelt shifts characteristic of abrupt events may have had an important impact on dust across the Atlantic region. Unlike for the glacial–interglacial difference, these faster, decadal to centennial scale transitions drive significant dust generation and meridional dust transport which enhances dust delivery over Greenland. These results help reconcile several features of the glacial dust cycle and thereby question the paradigm that Asian desert conditions can explain both modes of variability in Greenland dust records. The model points to a greater sensitivity of the poleward dust transport to climate change and provides a basis for investigating the potential role of dust radiative feedbacks during abrupt climate change.